Strategic Imperatives for the Post Covid-19 Era: With Special Focus on Sri Lankan Industries - R. A., Rajaratnam; A. P., Medis; D. M. R., Dissanayake (2020)
Strategies provide intent for organizations to drive their respective business models. The responsiveness to environment challenges and dynamics is a must for corporates to survive and grow even during turbulent conditions. The term „strategy‟ and its content had been associated in this paper to bridge the explanations and arguments on how strategy should be reshaped when totally unpredicted scenarios emerge. The Covid-19 outbreak provided a lesson, to the entire global market and to rethink the strategic intent of organizations. The strategic imperatives during the outbreak conditions should be carefully planned and implemented with rationalized business models. This paper attempts to investigate the strategic imperatives and how they need to be connected with proper scenario planning, resulting in a focused-strategic drive. Included are reviews on global business scenarios whilst highlighting some key incidents of global corporates and country situations. This paper provides a platform to understand how Covid-19 outbreak made holistic impacts on economies and societies that ultimately resulted in new-normal adaptation options for corporates. Authors undertook a literature review to unveil the empirical discussions whilst cases of Sri Lankan market were highlighted to explain the real life experiences on how local corporates adopted to new-normal scenarios. The best practices undertaken by Sri Lankan firms and industries were referred to generate a practise-related knowledge sharing. Finally, this paper concludes the essence of the paper, whilst proposing the importance of reviewing hands-on cases in Sri Lanka to share new knowledge insights to practitioners.